2022
DOI: 10.1002/jcla.24574
|View full text |Cite
|
Sign up to set email alerts
|

Detection of partial deletion and mosaicism using quantitative fluorescent polymerase chain reaction: Case reports and a review of the literature

Abstract: Background Aneuploidy of chromosomes 13, 18, 21, X, and Y can be detected by the quantitative fluorescence polymerase chain reaction (QF‐PCR) performed with short tandem repeat (STR) markers. Although QF‐PCR is designed to detect whole chromosome trisomy, the partial deletion or mosaic of chromosomes may also be detected. Methods Partial deletion or mosaic of chromosomes in three cases was detected by QF‐PCR. Karyotyping and chromosome microarray analysis(CMA) were performed. We further reviewed the clinical u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…However, QF-PCR cannot detect inversions or translocations. The deletion or duplication region outside the STR loci will also be missed[ 10 , 11 ]. Consequently, QF-PCR may overlook structural chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, QF-PCR cannot detect inversions or translocations. The deletion or duplication region outside the STR loci will also be missed[ 10 , 11 ]. Consequently, QF-PCR may overlook structural chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first case of Yp11.2 duplication that we have found among more than 3000 patients who have undergone QF-PCR in our laboratory. Previous studies have reported the function of QF-PCR in detecting mosaicism, deletions, or duplications[ 11 - 13 ]. These cases had deletion or duplication regions within the STR marker range designed in the QF-PCR kit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation